Tax Procedure Law within the Reduction of Administrative Burdens – between Goals and Praxis - Polona Kovač (Central European Public Administration Review)
The Tax Procedure Act (TPA; Slovenian ZDavP) is the key law regulating relations among the participants in tax collection procedures. Therefore, it has been more or less thoroughly changed several times in recent years, also within the government’s programme of reduction of administrative burdens (RAB; Slovenian OAO). Procedures are being attempted to be simplified for both taxpayers and tax authorities. The paper explores a selection of institutes introduced to this end, such as tax assessment through a provisional specification, service by regular mail, advance rulings, etc. The author considers statistical data on how frequently those (new) institutes were used in 2006, 2007 and 2008 to establish whether, or how much, goals of the regulatory change in the tax procedure are actually being achieved in praxis. It is found that notwithstanding some exceptions, the majority of the considered institutes do amount to a realisation of the RAB programme.